Study on Preparation of Highly Ordered Nanochannel Array Aluminium Oxide Template - Cheng, Fa-Liang; Jin, Bao-Kang; Wang, Hong; Wu, Jian; Zhang, Ming-Liang (Asian Journal of Chemistry, 2016)
A kind of big anodic aluminium oxide (AAO) templates with highly ordered nanochannel array has been prepared by two-step anodizing approach. Numerous conditions, e.g., anodic voltage, temperature, concentration of electrolyte and time have confirmed that 99.999% aluminium was anodized in 1.0 mol/L sulfuric acid electrolyte with 20 V steady potential at 0-5 ºC would produce the best microporous Al2O3. After removing the Al substrate and corrupting the barrier layer, the closely packed hexagonal monodisperse cylindrical nanochannel array was obtained with average porous diameter at 30 nm, channel length at about 30-40 mm and porous density at 4.8 × 1010 pores cm-2. The formation process and mechanism of the self organizing nanochannel array have been discussed in detail.